The COVID-19 pandemic in Norway and Sweden – threats, trust, and impact on daily life: a comparative survey - Helsingen, Lise M.; Refsum, Erle; Gjøstein, Dagrun Kyte; Løberg, Magnus; Bretthauer, Michael; Kalager, Mette; Emilsson, Louise (BMC public health, 2020)
Background Norway and Sweden have similar populations and health care systems, but different reactions to the COVID-19 pandemic. Norway closed educational institutions, and banned sports and cultural activities; Sweden kept most institutions and training facilities open. We aimed to compare peoples’ attitudes towards authorities and control measures, and perceived impact of the pandemic and implemented control measures on life in Norway and Sweden. Methods Anonymous web-based surveys for individuals age 15 or older distributed through Facebook using the snowball method, in Norway and Sweden from mid-March to mid-April, 2020. The survey contained questions about perceived threat of the pandemic, views on infection control measures, and impact on daily life. We performed descriptive analyses of the responses and compared the two countries. Results 3508 individuals participated in the survey (Norway 3000; Sweden 508). 79% were women, the majority were 30–49 years (Norway 60%; Sweden 47%), and about 45% of the participants in both countries had more than 4 years of higher education. Participants had high trust in the health services, but differed in the degree of trust in their government (High trust in Norway 17%; Sweden 37%). More Norwegians than Swedes agreed that school closure was a good measure (Norway 66%; Sweden 18%), that countries with open schools were irresponsible (Norway 65%; Sweden 23%), and that the threat from repercussions of the mitigation measures were large or very large (Norway 71%; Sweden 56%). Both countries had a high compliance with infection preventive measures (> 98%). Many lived a more sedentary life (Norway 69%; Sweden 50%) and ate more (Norway 44%; Sweden 33%) during the pandemic. Conclusion Sweden had more trust in the authorities, while Norwegians reported a more negative lifestyle during the pandemic. The level of trust in the health care system and self-reported compliance with preventive measures was high in both countries despite the differences in infection control measures.